An optimal production/maintenance planning under stochastic random demand, service level and failure rate - Zied, H.; Sofiene, D.; Nidhal, R. (2009 IEEE International Conference on Automation Science and Engineering, 2009)
This paper deals the combination between production and maintenance plan for a manufacturing system satisfying a random demand. A jointly optimization is made in order to establish an optimal production planning and scheduling maintenance strategy showing the machine degradation. The key of this study is to consider the influence of the production rate on the degradation degree. We prove simultaneously, with a constrained stochastic production-maintenance planning problem under hypotheses of inventory and failure rate variables, an optimal production plan and maintenance scheduling which minimizes the average total holding, production and maintenance costs. A numerical example is studied in order to apply the developed approach.